Digital Observation of Teacher Candidates: InTASC Accountability for CAEP - Kelly Gillespie; Sue Jenkins; Volora Hanzlicek (The Advocate, 2016)
Teacher preparation programs want to ensure accountability to InTASC and CAEP standard while simultaneously maximizing gains in the quality of instruction delivered by teacher candidates. The solution, research-based, digital observation to monitor classroom practice with expected outcomes; generate realtime data for self reflection and collaborative dialogue; and deliver instantaneous feedback for growth and continuous improvement. The research is clear. The number one factor affecting student learning is quality of teaching (“Teachers Matter,” 2012). The number one factor affecting quality of teaching is instructional conversations (Danielson, 2009). Instructional conversations must be based on data. The Digital eWalkThrough System generates these data.